(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objectives: To evaluate the association between short-term blood pressure variability (BPV) within 24 hours of admission and early functional outcomes in acute ischemic stroke (AIS) patients, and to identify specific time periods during which BPV most strongly predicts neurological deterioration. Design: Observational cohort study analyzing 24-hour blood pressure variability and its association with early outcomes in acute ischemic stroke patients. Place & duration of study: This single-center prospective observational cohort study was conducted at the Stroke Ward of the Department of Neurology, Shifa International Hospital, Islamabad, Pakistan. Between 06 April, 2024, and 06 April, 2025, consecutive patients with AIS admitted within 24 h of symptom onset were enrolled. Methodology: In 245 AIS patients, systolic and diastolic BPV—quantified as coefficient of variation (CV)—were analyzed across six time intervals. Outcomes included National Institutes of Health Stroke Scale (NIHSS) score ≥ 5 (poor outcome) at day 7 and Modified Rankin Scale (mRS) ≥ 3 (disability) at day 30. Logistic regression adjusted for age, sex, body mass index, smoking status, hypertension, diabetes mellitus, and coronary heart disease. Results: Higher diastolic blood pressure-CV during 4 pm–8 pm was significantly associated with poor outcomes at day 7 (unadjusted odds ratio [OR]: 2.109; 95% confidence interval [CI]: 1.160–3.834; p < 0.05), though significance attenuated after adjustment (OR: 1.846; 95% CI: 0.985–3.458). No BPV metrics predicted day-30 disability. Mean systolic and diastolic blood pressure-CV ranged from 2.54–4.96% across intervals (all p < 0.001 vs. baseline). Conclusion: Elevated diastolic BPV in the evening (4 pm–8 pm) may predict early neurological deterioration in AIS, warranting time-targeted blood pressure management.